Budgeting from the Point of View of Fiqh and Resistance Economy - Seyyed Alimohammad yasrebi; Mohammad Hadi Salimzadeh (پژوهش‌های فقهی مسائل مستحدثه, 2024)
Today, it is clear to all that the economy of the public sector and welfare economics are filled with normative discussions, and the relationship between law and economics cannot be denied in any way. One of the subjects that can be examined from an interdisciplinary perspective is government budgeting. The budget, as a policymaking tool at the government's disposal, seeks to allocate limited resources to unlimited needs and desires. Governments must adopt a purposeful approach in preparing and implementing the budget within the framework of the government's general policies. Resistance economy, as the main economic policy in the Islamic Republic of Iran, aims to transform existing economic structures and localize them based on its worldview and objectives. In this regard, the country's budgeting system must align with the principles of a resistance economy. Public funds, annual budgeting, the methods of resource mobilization and allocation, the criteria for effective governance, the role of the government in the economy, and the cultural and faith attachments are all crucial aspects of this discussion. The structured regulation of the foundations and purposes of an acceptable and robust budget, grounded in religious and scientific criteria with a focus on a resistance economy, represents a modest yet significant step in this direction. In summary, this paper discusses the concept of resistance economy, budgeting principles, operational budgeting, oversight, budget comparison, public funds, and the resources for their mobilization and allocation, along with conventional issues in both fields.